2002
DOI: 10.1046/j.1464-410x.2002.03035.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sodium transport in epithelial cells in a rat ileal‐augmented bladder model

Abstract: Objective To investigate changes in the morphology and sodium transport ability of intestinal epithelium diverted to the urinary tract, using an in vitro sodiumbinding benzofuran isophthalate (SBFI) technique, as the effects of long-term urine exposure on the transport of electrolytes through intestine are incompletely understood. Materials and methods Ileal augmentation cystoplasty was conducted in female Sprague-Dawley rats; at 3 and 12 months after surgery the serum concentration of sodium, chloride and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Acidosis results because intestinal segments retain their absorptive and secretory properties such as the absorption of ammonium, chloride, potassium and urea as well as the secretion of bicarbonate and sodium [8,10,13] . The frequency and severity of metabolic acidosis are mainly related to the type and length of the intestinal segment used [14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acidosis results because intestinal segments retain their absorptive and secretory properties such as the absorption of ammonium, chloride, potassium and urea as well as the secretion of bicarbonate and sodium [8,10,13] . The frequency and severity of metabolic acidosis are mainly related to the type and length of the intestinal segment used [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Bladder augmentation predisposes the patient to many adverse events such as infections, bladder stones, hyperchloremic metabolic acidosis and even cancers [8][9][10] . In this regard, an incidence of transitional cell carcinoma of 4-27% is reported and an incidence of proliferative lesions in 36-54% of ileocystoplasty in rats [7,11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various complications associated with urinary diversion have been extensively reported 1,2 . Furthermore, several investigators have performed basic experiments to address these complications 3–5 . For example, Fujisawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fujisawa et al . showed that sodium transport was significantly decreased in the ileal epithelium of a rat bladder augmentation model and concluded that the improvement in metabolic change was probably attributable to alterations of electrolyte transport and atrophic changes of the villus 5 . However, to our knowledge, there has not been a study globally analyzing the effect of the long‐term exposure of the intestinal segment to urine at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation